Prediction of the acceleration and stopping manoeuvres of a bare hull surface combatant by closed-form solutions and CFD - Duman, Suleyman; Bal, Sakir (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, the acceleration and stopping manoeuvres of a bare hull surface combatant have practically been predicted by closed-form (analytical) solutions derived from basic mechanical principles. They have also been simulated directly by an unsteady RANS (Reynolds-averaged Navier-Stokes) solver with overset grid structure to compare the results with those of closed-form approaches. A well-known surface combatant model DTMB5415 has been chosen for validation. The instantaneous drag forces of the model ship in the acceleration and stopping manoeuvres have been provided by both CFD and Holtrop's methods. It has been observed that the results by analytical solutions have a good match with those of the manoeuvring simulations based on unsteady RANS solver. Successful predictions have also been made consistent with the results obtained when experimental resistance values are used in analytical solutions. It has been concluded that the closed-form solution methods yield practically satisfactory results in a very short time when a fast resistance prediction method, such as Holtrop's method or CFD, is used.
Keywords: Ship manoeuvring; Acceleration; Stopping; CFD; Analytical solution; PERFORMANCE; Engineering; Oceanography